Chaos, complexity and computation in the evolution of biological systems. (July 2022) - Cottam, Ron; Vounckx, Roger
Abstract: Chaos, complexity and computation are especially important concepts with respect to both the Evolution of biological systems and the evolution of the Universe. We consider each of these five entities separately, and then view their combination in an overall consideration of both evolution and Evolution. The concept of computation can be directly derived from processes characteristic of the Evolution of biology or the evolution of the Universe, rather than presumed from our own mathematical ideas. We advocate the inclusion of meaning in science's deliberations, and support this by insisting that physically embodied abstractions should be considered part concrete in character. Combination of our initial five conceptual entities indicates that biological Evolution follows the same developmental criteria as the evolution of the Universe, albeit with an intermediate change in strategy. We conclude that evolutionarily derived computation is the prime driver of evolution/Evolutions' implications.